Polymorphism of TPH2 gene rs120074175 is not associated with risk factors of schizophrenia - James P Laksono; Riyadi Sumirtanurdin; Haafizah Dania; Fitri N Ramadhani; Dyah A Perwitasari; Rizky Abdulah; Melisa I Barliana (Wolters Kluwer Medknow Publications, 2019)
Context: Polymorphism on tryptophan hydroxylase 2 (TPH2) gene rs120074175 can cause the synthesis of neurotransmitter serotonin in the brain to reduce up to 80%. Reduced serotonin in the brain can cause dopamine release to occur continuously. Excess dopamine in the brain may cause positive symptom of schizophrenia. Aim: The aim of this study was to investigate the genotype distribution of TPH2 rs120074175 gene on patients with schizophrenia at Prof. Dr. Soerojo Magelang Psychiatric Hospital, Indonesia, and the relationship between the genetic polymorphism of the TPH2 rs120074175 gene against risk factors of schizophrenia. Settings and Design: This was a cross-sectional study. Materials and Methods: The method used was amplification refractory mutation system-polymerase chain reaction (ARMS-PCR). Whole blood from healthy subjects and patients with schizophrenia, Wizard genomic deoxyribonucleic acid (DNA) purification kit (Promega, Fitchburg, Wisconsin), PCR master mix (Promega), ARMS-PCR primers, ddH2O, agarose (Thermo Scientific, Seoul, South Korea), Tris, Acetic Acid, EDTA (TAE) 1X, ethidium bromide, loading dye 6×, and DNA ladder (Thermo Scientific) were the materials used. Statistical Analysis: Hardy-Weinberg equilibrium and chi-square (χ2) tests were used. Results: The results showed that both groups (healthy subjects and patients with schizophrenia) at the Prof. Dr. Soerojo Magelang Psychiatric Hospital have a wild-type GG genotype (100%) without anyone having a mutant A allele. Conclusion: TPH2 rs120074175 gene polymorphism was not associated with risk factors for schizophrenia.